IMPLEMENTASI MODEL PEMBELAJARAN MEANINGFUL INSTRUCTION DESIGN (MID) UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS SISWA PADA MATERI OPERASI ALJABAR KELAS VII - Yartati, Rosmini; Prihatiningtyas, Nindy Citro; Mariyam, Mariyam (Universitas Islam Sumatera Utara, 2024)
The purpose of this study was to determine the implementation of meaningful instruction design (MID) learning model to improve students' mathematical literacy in algebraic operation material in class VII SMP 5 Salatiga. This study used a quasi-experimental model with a sample of 30 people. The instruments used were in the form of tests totalling 3 questions for the pre-test and post-test. The results obtained from this study are that by using the mann whitney test there is a difference in the improvement of students' mathematical literacy skills between those using the MID Learning Model and by using learning with a scientific approach to the material of algebraic operations, it is concluded that student learning motivation for positive and negative statements on all indicators is on high criteria with a total of 15 students resulting in an overall average of 3.97 students with high criteria; the average percentage of implementation at the first and second meetings obtained a percentage of 87.698% at the first meeting and 87.302% at the second meeting; and the increase that occurred in the experimental class was in the medium category and in the control class was in the low category. Thus, it can be concluded that the implementation of learning is good when the MID Learning Model is applied to the material of algebraic operations in class VII at SMP Negeri 5 Salatiga.